Safety application of muscle relaxants and the traditional low-frequency ventilation during the flexible or rigid bronchoscopy in patients with central airway obstruction: a retrospective observational study - Li, Jing-Jin; Li, Nan; Ma, Wei-Jia; Bao, Ming-Xue; Chen, Zi-Yang; Ding, Zheng-Nian (BMC anesthesiology, 2021)
Bronchoscopy treatments of central airway obstruction (CAO) under general anesthesia are high-risky procedures, and posing a giant challenge to the anesthesiologists. We summarized and analyzed our clinical experience in patients with CAO undergoing flexible or rigid bronchoscopy, to estimate the safety of skeletal muscle relaxants application and the traditional Low-frequency ventilation. Clinical data of 375 patients with CAO who underwent urgent endoscopic treatments in general anesthesia from January 2016 to October 2019 were retrospectively reviewed. The use ratio of skeletal muscle relaxants, dose of skeletal muscle relaxants used, the incidence of perioperative adverse events, adequacy of ventilation and gas exchange, post-operative recovery between rigid bronchoscopy and flexible bronchoscopy therapy, and risk factors for postoperative ICU admission were evaluated. Of the 375 patients with CAO, 204 patients were treated with flexible bronchoscopy and 171 patients were treated with rigid bronchoscopy. Muscle relaxants were used in 362 of 375 patients (including 313 cisatracurium, 45 rocuronium, 4 atracurium, and 13 unrecorded). The usage rate of muscle relaxants (96.5% in total) was very high in patients with CAO who underwent either flexible bronchoscopy (96.6%) or rigid bronchoscopy (96.5%) therapy. The dosage of skeletal muscle relaxants (Cisatracium) used was higher in rigid bronchoscopy compared with flexible bronchoscopy therapy (10.8 ± 3.8 VS 11.6 ± 3.6 mg, respectively, p < 0.05). No patient suffered the failure of ventilation, bronchospasm and intraoperative cough either in flexible or rigid bronchoscopy therapy. Hypoxemia was occurred in 13 patients (8 in flexible, 5 in rigid bronchoscopy) during the procedure, and reintubation after extubation happened in 2 patients with flexible bronchoscopy. Sufficient ventilation was successfully established using the traditional Low-frequency ventilation with no significant carbon dioxide accumulation and hypoxemia occurred both in flexible and rigid bronchoscopy group (p > 0.05). Three patients (1 in flexible and 2 in rigid) died, during the post-operative recovery, and the higher grade of American Society of Anesthesiologists (ASA) and obvious dyspnea or orthopnea were the independent risk factors for postoperative ICU admission. The muscle relaxants and low-frequency traditional ventilation can be safely used both in flexible and rigid bronchoscopy treatments in patients with CAO. These results may provide strong clinical evidence for optimizing the anesthesia management of bronchoscopy for these patients.